Pengaruh Media Tanam dan Jamur pada Tanaman Johar (Senna siamea) di Pembibitan PT Asmin Bara Bronang: The Effect of Planting Media and Fungi on Johar Plants (Senna siamea) at PT Asmin Bara Bronang Nursery - Leonardus Indrianto; Hasan Mudzakir; Suwityo Setyo Budi; Rodhi Tri D; M. Akbar Ogy D; Rafinoza Rafinoza; Ucok Ali M H.; Bhra Jalesvianto Basuki; Farizalman Aria Bima; Riza Zainuddin Ahmad (JURNAL HUTAN TROPIKA, 2026)
Johar (Senna siamea) plants are a choice for revegetation in reclaimed land due to their ability to grow in general reclaimed land soil conditions. Then, an experiment was conducted to plant these plants using Discard Washing Coal and CPP Sediment planting media, which are often found in coal mining processing, while compost and cocopeat planting media were used as controls. A total of 90 Johar plants were planted in these media in polybags (30 cm x 18 cm) with the treatments Johar A (Discard Washing Coal media + mushrooms); Johar B (CPP sediment media + mushrooms) and Johar C (soil:compost:cocopeat media = 1:1:1 + mushrooms) maintained for 12 weeks and observed weekly for stem height and stem diameter growth. The test was carried out with 30 replications. The results obtained only showed a significant difference (p <0.05) in stem height growth of Johar C and B, while other observations did not differ. The conclusion is that Johar C media (control) media containing soil, compost, and cocopeat is the best growth medium for Johar plants.